2019
DOI: 10.1002/art.41031
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Certolizumab Pegol, Abatacept, and Biosimilar Infliximab in Patients With Rheumatoid Arthritis Treated in Routine Care: Observational Data From the Danish DANBIO Registry Emulating a Randomized Trial

Abstract: Objective. Nationwide Danish guidelines regarding rheumatoid arthritis (RA) patients initiating biologic treatment (i.e., biologic disease-modifying antirheumatic drugs [DMARDs]) are issued on an approximately annual basis. For biologics-naive patients treated with concomitant methotrexate, mandatory medications included certolizumab pegol (CZP; year 2013-2014, recommended compliance 80%), abatacept (ABA; 2014-2015, 80%), and biosimilar infliximab (CT-P13; 2015. We hypothesized that these guidelines could be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…One-hundred and fifteen studies (58%) completely reported how the target trial protocol was emulated. Eighty-seven studies (44%) provided both the protocol of the target trial and described how it was emulated (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 50 However, lack of randomization makes observational effect estimates vulnerable to confounding. 66 …”
Section: Resultsmentioning
confidence: 99%